2004
DOI: 10.1093/nar/gkh999
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of translocation by Type I restriction-modification enzymes is associated with a short DNA extrusion

Abstract: Recognition of 'foreign' DNA by Type I restriction-modification (R-M) enzymes elicits an ATP-dependent switch from methylase to endonuclease activity, which involves DNA translocation by the restriction subunit HsdR. Type I R-M enzymes are composed of three (Hsd) subunits with a stoichiometry of HsdR2:HsdM2:HsdS1 (R2-complex). However, the EcoR124I R-M enzyme can also exist as a cleavage deficient, sub-assembly of HsdR1:HsdM2:HsdS1 (R1-complex). ATPS was used to trap initial translocation complexes, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 23 publications
(32 reference statements)
0
42
2
Order By: Relevance
“…Tracking of the DNA helix will cause the generation of negative supercoiling in the expanding loop, at a rate of one superhelical twist per helical repeat (10.5 bp for B-form DNA) and should be sufficient to block translocation (2). Some supercoiled structures have been observed in AFM images of EcoR124I (15) and in electron microscope images of EcoKI and EcoBI (16). However, not all loops exhibited supercoiling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tracking of the DNA helix will cause the generation of negative supercoiling in the expanding loop, at a rate of one superhelical twist per helical repeat (10.5 bp for B-form DNA) and should be sufficient to block translocation (2). Some supercoiled structures have been observed in AFM images of EcoR124I (15) and in electron microscope images of EcoKI and EcoBI (16). However, not all loops exhibited supercoiling.…”
mentioning
confidence: 99%
“…Supercoiling will pose the largest barrier to translocation for small loops, because the superhelical density will be largest immediately after translocation initiation. It has been proposed that this barrier may be overcome by melting the DNA during translocation initiation (15), or by the formation of a (relaxed) diffusive loop before translocation, which will reduce the superhelical density (17). Translocation rates of up to 550 bp/s have been reported for type I enzymes, such as EcoR124I (18,19).…”
mentioning
confidence: 99%
“…3A and unpublished results), hinting that ssDNA encountered by PrrC in the uninfected cell helps silence the ACNase. Second, the type Ic DNA R-M protein EcoR124I unwinds short DNA stretches flanking its target sequence (van Noort et al, 2004;Stanley et al, 2006), suggesting a possible source for the putative ACNase-inhibiting ssDNA. Third, within a latent ACNase complex tethered to an EcoprrI DNA ligand PrrC was UV-crosslinked to DNA regions flanking EcoprrI's recognition site (Fig.…”
Section: Players In Prrc's Silencing and Activationmentioning
confidence: 99%
“…This exciting work points toward potential uses for this type I R-M enzyme as a nanoactuator within a biosensor (64) in the field of bionanotechnology, something we could hardly have believed possible in the early 1970s when this work started. In fact, in the early 1970s, it was impossible to imagine that it would be possible to measure DNA translocation for a single molecule let alone show that the motor could pull a micrometer-sized magnetic bead over a distance of several micrometers, an amazing capability for a motor measuring only a few nanometers in diameter (90).…”
Section: Single-molecule Studies With the Ecor124i Molecular Machinementioning
confidence: 99%
“…Footprinting studies have shown that the endonuclease does not "reach" over such a distance (57,66), yet the enzyme can somehow "bend" adjacent DNA to initiate translocation despite the large energy input required. Studies using scanning probe microscopy by van Noort et al (90) demonstrated that the DNA in the initial complex (captured using a nonhydrolyzable analogue of ATP) was present as a single-stranded DNA bulge, one strand of which was visible in the scanning probe microscopy and accessible to single-strand-specific nucleases and the other of which was buried in the enzyme. Therefore, the motor is able to "melt" DNA adjacent to its binding site and hold these strands apart prior to translocation.…”
Section: Single-molecule Studies With the Ecor124i Molecular Machinementioning
confidence: 99%